Analyst Recommendations: Is Singapore Strong-Form Efficient? - Chow, Kar Tzen (2007)
The investment value of analysts’ recommendations in Singapore is investigated by conducting an event study as well as an investor-oriented trading strategy based on the recommendations. The event study on 1897 analyst reports produced over a one year period document significant abnormal returns in the event window surrounding the analysts’ recommendations. This leads to the conclusion that research analysts play a role in enhancing the informational efficiency of the equities markets. Furthermore with significant post-recommendation ‘drifting’ in abnormal returns observed it is suggested that the analysts’ have market timing and stock picking abilities. Significant pre-event abnormal returns were also recorded suggesting that there might be internal leakage of information prior to release of the analysts’ recommendations. Cross-sectional analyses carried out on the Buy recommendations found a monotonic rise in abnormal returns going from reiterations to upgrades to initiations. It was also observed that smaller capitalization firms delivered higher abnormal returns than larger firms. Analysts’ target prices were also shown to give incremental information above that of their recommendations. Comparing the impact of foreign versus local research firms’ recommendations, results show the local firms having more if not the same impact as their foreign counterparts. Applying an investor-oriented trading strategy, it was found that investors with access to the analysts’ recommendations stand to seize significant abnormal returns net of transactions costs. This leads us to reject the strong-form Efficient Market Hypothesis for the Singapore equity market.